CT And MRI Measurements Of Tibial Tubercle To Trochlear Groove Distances (TT-TG) Are Not Equivalent - Camp, Christopher L. (Orthop J Sports Med, 2013)
OBJECTIVES: TT-TG distance is a commonly used measurement for surgical decision-making in patients with patellofemoral malalignment and instability. This measurement has historically been performed utilizing axial CT scans. More recently, MRI has been proposed as an equivalent test for measurement of TT-TG distance. We sought to determine the reliability of TT-TG measurements on both MRI and CT, and to determine whether the measurements can be used interchangeably. METHODS: All patients diagnosed with patellar instability who had received both CT and MRI of the knee between 2003 and 2011 were included (n=59 knees in 54 patients). Two fellowship trained musculoskeletal radiologists measured the TT-TG distances for each patient by CT and MRI in a randomized, blinded fashion for a total of 236 measurements. Inter-observer reliability was calculated between radiologists for both imaging modalities and inter-methods reliability was calculated between the two imagining modalities. The results are reported using intraclass correlation coefficients (ICC) and Bland Altman analysis (BAA). RESULTS: The 59 knees had a mean TT-TG distance of 16.9 mm (range: 8.3-25.8) by CT and 14.7 mm (range: 1.5-25.1) by MRI. Eighteen patients (31%) had a TT-TG ≥ 20 mm by CT, and only 9 (15%) had a TT-TG ≥ 20 mm by MRI. Inter-observer reliability between the radiologists was considered excellent for both CT and MRI (ICC = 0.777 and 0.843 respectively). When comparing CT to MRI, however, the ICC was considered only fair for each of the two raters (0.532 and 0.539). A total of 11 patients (19%) had a TT-TG ≥ 20 mm on CT preoperatively and underwent distal realignment by tibial tubercle osteotomy (TTO). In this surgical subgroup, the mean TT-TG on CT was 22.5 mm (range 19.8-25.8) while the mean TT-TG on MRI was only 18.7 mm (range 14.4-22.8). CONCLUSION: TT-TG distance can be measured with excellent inter-rater reliability on both MRI and CT scans; however, the values derived from these two tests may not be interchangeable. This observation should be taken into consideration when MRI is used for surgical planning since MRI may underestimate TT-TG distance when compared to CT.